2006
DOI: 10.1029/2006gl026229
|View full text |Cite
|
Sign up to set email alerts
|

Current sheets at low altitudes in the Martian magnetotail

Abstract: We present observations of 1116 current sheet crossings in the Martian magnetotail during one Martian year, as identified from magnetic field rotations measured by Mars Global Surveyor (MGS) at ∼400 km altitude and 2 am local time. Crossings are observed everywhere except above strong crustal fields, and many occur in clusters, with preferred locations varying as a function of season and IMF draping direction. Magnetic polarities are consistent with day‐side IMF draping directions and a two‐lobe induced magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 17 publications
7
56
1
1
Order By: Relevance
“…Based on considerations of geometry, it seems more likely that these flux ropes are being generated sequentially at a single site rather than by the simultaneous formation of multiple X-lines. Although observations of this type are quite rare in MGS data, this event is not unique; in a database of 1116 MGS magnetotail current sheet crossings [Halekas et al, 2006], we have identified 45 examples where multiple flux ropes were observed, however the event presented here is the cleanest example.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Based on considerations of geometry, it seems more likely that these flux ropes are being generated sequentially at a single site rather than by the simultaneous formation of multiple X-lines. Although observations of this type are quite rare in MGS data, this event is not unique; in a database of 1116 MGS magnetotail current sheet crossings [Halekas et al, 2006], we have identified 45 examples where multiple flux ropes were observed, however the event presented here is the cleanest example.…”
Section: Discussionmentioning
confidence: 79%
“…The magnetotail is a region through which there is significant escape of ionospheric material [Lundin et al, 2008], and so it is important to ascertain the extent to which magnetotail dynamics may inhibit or enhance the transport of planetary plasma away from Mars. In particular, within the magnetotail is found the magnetotail current sheet, separating the two hemispheres of draped solar wind magnetic field [Halekas et al, 2006]. The interaction between crustal fields and the draped field can lead to the formation and detachment of large magnetic flux ropes enabling the bulk removal of material [Harnett, 2009;Brain et al, 2010;Morgan et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of field aligned currents have been infered from observations of perturbations in the magnetic field near magnetic cusps Halekas et al, 2006). The magnitude of these currents are ∼0.5 to 1 μA m −2 .…”
Section: Discussionmentioning
confidence: 99%
“…For the smaller bodies, Mars and Titan, the grid size is often smaller than the ion skin depth and boundary layers of the interaction can be resolved. For example, the thickness of the bow shock and magnetic pile-up boundary at Mars and Venus are on the order of the ion skin depth (Mazelle et al 2004) as is the current sheet thickness at Titan and Mars (Halekas et al 2006;Wahlund et al 2005). However, resolving the ion skin depth violates the assumptions of some models.…”
Section: Assumptions Of Mhd Modelsmentioning
confidence: 99%